2012
DOI: 10.1172/jci58762
|View full text |Cite
|
Sign up to set email alerts
|

Protective antifungal memory CD8+ T cells are maintained in the absence of CD4+ T cell help and cognate antigen in mice

Abstract: Individuals who are immunocompromised, including AIDS patients with few CD4 + T cells, are at increased risk for opportunistic fungal infections. The incidence of such infections is increasing worldwide, meaning that the need for antifungal vaccines is increasing. Although CD4 + T cells play a dominant role in resistance to many pathogenic fungal infections, we have previously shown that vaccination can induce protective antifungal CD8 + T cell immunity in the absence of CD4 + T cells. However, it has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 59 publications
2
70
0
1
Order By: Relevance
“…These data are supported by several papers that demonstrate that activated CD8 ϩ T cells are critical for host-mediated defense against other fungal pathogens (52, 53). Additionally, these data suggest that an immunocompromised host may be treated for fungal infections by the direct targeting of IFN-␥-secreting CD8 ϩ T cells (4,26,39,54). However, we cannot exclude the possibility that IL-7 treatment promotes macrophage-mediated killing and/or enhances the P. murina-specific antibody response.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…These data are supported by several papers that demonstrate that activated CD8 ϩ T cells are critical for host-mediated defense against other fungal pathogens (52, 53). Additionally, these data suggest that an immunocompromised host may be treated for fungal infections by the direct targeting of IFN-␥-secreting CD8 ϩ T cells (4,26,39,54). However, we cannot exclude the possibility that IL-7 treatment promotes macrophage-mediated killing and/or enhances the P. murina-specific antibody response.…”
Section: Figmentioning
confidence: 94%
“…While several studies have demonstrated that CD4 ϩ T cells are crucial for resistance to fungal infection (39)(40)(41), less is known about CD8 ϩ T cells. We have previously demonstrated that both CD4 and CD8 T cells are important for host defense against Pneumocystis (4).…”
Section: Fig 7 Cd8mentioning
confidence: 99%
“…Though CD4 + T cells play the major role regarding control of pathogenic fungal infections, it was demonstrated in a murine model infected with yeasts that protective antifungal memory CD8 + T cells persisted for more than 5 months without CD4 + T cell help and remained fully functional [72]. Earlier studies in mice and human peripheral blood mononuclear cells also illustrated that CD8 + T cells mount protective antifungal immune responses [73].…”
Section: Cd4mentioning
confidence: 99%
“…Th1 and Th17 cells mediate protection in fungal infections and vaccination through a variety of antifungal effector mechanisms, Th22 cells are strictly required for antifungal resistance at mucosal surfaces, and Th2 cells may dampen inflammation [7,10]. Memory CD8 + cytotoxic T cells are also induced in fungal infections [7,33,34] and mediate protection via the production of IFN-g and cytolytic activity against fungus-laden cells or the fungus itself [23,24], thus exhibiting polyfunctional activity ( Figure 1). As such, CD8 + T cells are ideal candidates to protect at mucosal surfaces.…”
Section: From Memory To Vaccinesmentioning
confidence: 99%